D6.9 ATHENA’s printed brochure - Hadjimitsis, Diofantos G.; Agapiou, Athos; Lysandrou, Vasiliki; Nisantzi, Argyro; Themistocleous, Kyriacos; Mettas, Christodoulos; Evagorou, Evagoras G.; Papoutsa, Christiana; Christofe, Andreas; Tzouvaras, Marios; Lasaponara, Rosa; Masini, Nicola; et al. (My University, 2018)
The specific deliverable displays the brochures of the ATHENA project which have been created, printed and distributed throughout the project, for dissemination purposes.
Keywords: Brochures; ATHENA project